Swimmers, Dancers - Leggott, Michele (Auckland University Press, 2013)
Swimmers, Dancers is a second collection of poems from Michele Leggott and is a tender evocation of family in free open verse that is full of colour, movement and light. The poems remember her parents and childhood, celebrate the birth of Leggott's second son and offer glimpses of art and literature amidst endless inventive games with words, sounds and spaces.